IFN-gamma stimulation of dental follicle mesenchymal stem cells modulates immune response of CD4(+) T lymphocytes in Der p1(+) asthmatic patients in vitro - AKKOÇ, TUNÇ (ELSEVIER ESPANA SLU, 2019)
Background: House dust mite (Dermataphagoides pteronyssinus) is a widespread risk factor in the development of asthma. CD4(+) T lymphocytes have an important role in the pathogenesis of allergic asthma by polarizing to Th2 cells. Objective: We aimed to evaluate the immunoregulatory effects of dental follicle mesenchymal stem cells with and without IFN-gamma stimulation on peripheral blood mononuclear cells of house dust mite sensitive asthmatic patients, and compared those with Dexamethasone as a systemic steroid. Material and methods: PBMC of asthmatic patients and healthy individuals separately cultured with or without DF-MSCs in the presence and absence of IFN-gamma or Der p1 or Dexamethasone for 72 h. CD4(+) T proliferation, cell viability, CD4(+)CD25(+)FoxP3(+) Treg cell frequency and cytokine profiles of PBMC were evaluated via flow cytometry. Results: DF-MSCs suppressed proliferation of CD4(+) T lymphocytes (p(CDmix) < 0.01, p(Derp1) < 0.01, p(IFN) < 0.005) by increasing the number of FoxP3 expressing CD4(+)CD25(+) T regulatory cells (p(CDmix) < 0.005, p(Derp1) < 0.01, p(IFN) < 0.001) and suppressed lymphocyte apoptosis (p(CDmix) < 0.05, p(Derp1) < 0.05, p(IFN) < 0.05), while Dexamethasone increased the apoptosis and decreased Treg cell frequency in asthmatic patients. IFN-gamma stimulation increased the suppressive effect of DF-MSCs and also enhanced the frequency of FoxP3 expressing CD4(+)CD25(+) T regulatory cells. The cytokine levels were regulated by DF-MSCs by reducing IL-4 cytokine levels (p(CDmix) < 0.01, p(Derp1) < 0.05, p(IFN) < 0.05) and upregulating IFN-gamma levels (p(CDmix) < 0.01, p(Derp1) < 0.05, p(IFN) < 0.005) in asthmatic patients. Conclusion: IFN-gamma stimulated DF-MSCs were found to have a high modulatory effect on CD4(+) T cell responses, while Dexamethasone had an apoptotic effect on CD4(+) T cells in asthmatic patients. DF-MSCs may be a new cell-based therapy option for allergic diseases including asthma. (C) 2019 SEICAP. Published by Elsevier Espana, S.L.U. All rights reserved.
Keywords: Dental follicle mesenchymal stem cells; Asthma; House dust mite; Der p1; INTERFERON-GAMMA; COCKROACH ALLERGEN; INFLAMMATION; EPITHELIUM; PATHOLOGY; EXPOSURE; CHILDREN